Addressing the present and the future in government and governance: three approaches to organising public action - Thynne, Ian; PetersIan, B. Guy Peters (2015)
Because public action matters in all countries and political systems, how it is organised now and in the future must exercise the minds of policy-makers in and beyond government. In response, we argue that there is considerable merit in having a widely applicable analytical lens through which to look at and assess present arrangements and future possibilities. The lens has multiple dimensions, which we address here in terms of three broad approaches to organising public action. We label these approaches as statism, state market dualism and statemarket civil society synergism. Their components and distinctive features are discussed, followed by a consideration of significant application issues and concerns. A fundamental matter is how best to balance the demands of public action and organised responses with the requirements of publicness and legitimacy as systems of government and governance are maintained and reformed. - Reproduced.
Keywords: Public administration